Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T14:37:18+01:00
A)
1/3x + 1/4 = 1/4x - 2/3
1/3x - 1/4x = -2/3 - 1/4
4/12x - 3/12x= -8/12 - 3/12
1/12x = -11/12
x = -11

b)
2 (x + 4) - 6 = 3 (x - 2) + 7x
2x + 8 - 6 = 3x - 6 + 7x
2x + 2 = 10x - 6
8x = 8
x = 1

c)
3/5x + 1 = 2
3/5x = 1
3x = 5
x = 5/3
1 5 1
2010-03-16T14:44:15+01:00
A)
1/3x+1/4=1/4x-2/3
1/3x-1/4x=-2/3-1/4
4/12x-3/12x=-8/12-3/12
1/12x=-11/12 /: 1/12
x=-11

spr
1/3*(-11)+1/4=1/4*(-11)-2/3
-11/3+1/4=-11/4-2/3
-44/12+3/12=-33/12-8/12
-41/12=-44/12
L=P

b)
2 (x + 4) - 6 = 3 (x - 2) + 7x
2x+8-6=3x-6+7x
2x-10x=-6-2
-8x=-8/:(-8)
x=1

spr
2(1+4)-6=3(1-2)+7*1
2*5-6=3*(-1)+7
4=4
L=P

c)
⅗ x + 1 = 2
3/5x=2-1
3/5x=1 /: 3/5
x=5/3
x=1i 2/3
spr
3/5 * 5/3+1=2
1+1=2
2=2
L=P
2010-03-16T14:45:01+01:00
A)⅓ x + ¼ = ¼ x - ⅔/*12
1/3x + 1/4 = 1/4x - 2/3
1/3x - 1/4x = -2/3 - 1/4
4/12x - 3/12x= -8/12 - 3/12
1/12x = -11/12
x = -11
b) 2 (x + 4) - 6 = 3 (x - 2) + 7x
2x+8-6=3x-6+7x
-8x=-8/*(-1)
x=1
2x+8-6=3x-6+7x
2*1+8*1-6=3*1-6+7*1
4=4
c) ⅗ x + 1 = 2 /*5
3x+5=10
3x=10-5
x=5/3